SYSTEM OF AGRICULTURAL STRUCTURAL PENSIONS IN POLAND AFTER THE YEAR 2000 BASED ON THE EXAMPLE OF THE SELECTED COUNTIES IN WARMIŃSKO-MAZURSKIE AND MAZOWIECKIE VOIVODSHIPS - Kisiel, Roman; Lech, Anna; Zawierucha, Kamila (Acta Scientiarum Polonorum. Oeconomia, 2011)
The aim of the survey was to conduct evaluation of functioning of the system of agricultural structural pensions in Poland (on the base of the secondary data originating from the Agency for Restructuring and Modernisation of Agriculture and Ministry of Agriculture and Rural Development) and the process of application for the structural pension from the perspective of the beneficiary (own survey). The questionnaire based survey covered 59 agricultural farms in Warmińsko-Mazurskie voivodship and 26 farms from Ciechanów County (Mazowieckie voivodship).